2006
DOI: 10.1002/jnr.21149
|View full text |Cite
|
Sign up to set email alerts
|

How does alcohol impair neuronal migration?

Abstract: Maternal alcohol consumption during pregnancy can cause serious birth defects, of which fetal alcohol syndrome (FAS) is the most devastating. Recognized by characteristic craniofacial abnormalities and growth deficiency, this condition produces severe alcohol-induced damage in the developing brain. FAS children experience ataxia; deficits in intellectual functioning; and difficulties in learning, memory, problem solving, and attention. Multiple aspects of central nervous system development can be affected by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 49 publications
2
46
1
1
Order By: Relevance
“…6A), this mechanism can be ruled out. Some studies have found increased cAMP levels or PKA activity in FAS (45,46); this would lead to an increased calcium current (41), so this mechanism can also be ruled out in our model because a reduction of the calcium current was observed. The activity of G proteins appears unchanged in FAS (47).…”
Section: Discussionmentioning
confidence: 87%
“…6A), this mechanism can be ruled out. Some studies have found increased cAMP levels or PKA activity in FAS (45,46); this would lead to an increased calcium current (41), so this mechanism can also be ruled out in our model because a reduction of the calcium current was observed. The activity of G proteins appears unchanged in FAS (47).…”
Section: Discussionmentioning
confidence: 87%
“…This information is consistent with the fi ndings of Coriale et al 3 Impairments of verbal and non-verbal intelligence in the exposed samples were presented in several studies. 13,20,25,37,41,42 The verbal and non-verbal IQ were equally impaired 38,39 and with an undefi ned consistent pattern. 36 A study by Nash et al 32 also highlighted this diffi culty in both areas and the same study also emphasized that impairment in the verbal domain becomes increasingly pronounced with advancing age.…”
Section: General Intelligencementioning
confidence: 97%
“…However, a hint of the relevance of alterations in calcium signalling in cortical pathologies linked to impaired neuronal migration emerges not from genetic mutations, but from environmental perturbations: Kumada et al [99] have shown that foetal alcohol syndrome (FAS), a serious disorder of brain development caused by maternal alcohol abuse during pregnancy, and other related disturbances, are linked to reduced calcium transients frequency and migratory activity of cerebellar granule cells; caffeine (1mM), by stimulating release form intracellular stores, and NMDA (30 µM), by inducing Ca 2+ influx, significantly reduced the effects of ethanol (25-100 mM) on the Ca 2+ transients and on migration. Similar effects were observed following inhibition of the cAMP pathway.…”
Section: Calcium Signalling and Neuronal Migration Disordersmentioning
confidence: 99%